Evaluasi Postur Kerja Pemotongan Tahu Menggunakan Metode RULA di UMKM Handayani - Devina Chalifatunnisa; Safarudin Ramdhani (Universitas Negeri Gorontalo, 2025)
MSMEs are one of the main pillars of Indonesia's economic growth, especially in the food sector. However, many production processes are still carried out manually and are not ergonomic. One such example is Mrs. Hj. Handayani's tofu MSME, where the manual tofu cutting process causes a non-ideal working posture and risks causing Musculoskeletal Disorders (MSDs). This study aims to initiate posture work using the Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA) methods, as well as designing an ergonomic cutting tool based on a pneumatic system adapted to local anthropometric data. The evaluation was conducted on one worker through direct observation and body angle analysis using Angulus and CATIA V5 software. The initial analysis results showed an NBM score of 57 and a RULA score of 6, indicating the need for work posture improvements in the near future. After the implementation of the tool, the RULA score decreased to 2 and cutting time was reduced by 45%, proving the tool's effectiveness in improving ergonomics and work productivity in the MSME environment.